Newly Synthesized Nonvacuum Processed High‐k Polymeric Dielectrics with Carboxyl Functionality for Highly Stable Operating Printed Transistor Applications. (23rd October 2020) - Kwon, Hyeok‐jin; Ye, Heqing; Shim, Kyuwon; Girma, Henok Getachew; Tang, Xiaowu; Lim, Bogyu; Kim, Yejin; Lee, Jihoon; Park, Chan Eon; Jung, Seo‐Hyun; Park, Jong Mok; Jung, Yu Jin; et al.
Abstract: Solution‐processed polar hydroxyl containing polymers such as poly(4‐vinylphenol) are widely utilized in organic filed‐effect transistors (OFETs) due to their high dielectric constant (k) and excellent insulating properties owing to the crosslinking through their hydroxyl groups. However, hydroxyl functionalities can function as trapsites, and their crosslinking reactions decrease the k value of materials. Hence, in this study, new solution‐processable copolymers containing both carboxyl and hydrophobic functionalities are synthesized. A fluorophenyl azide (FPA) based UV‐assisted crosslinker is also employed to promote the movement of polar carboxyl groups toward the bulk region and the hydrophobic functionalities to the surface region, thereby maintaining the high‐k characteristics and hydrophobic surface in thin film. Thus, the addition of an FPA crosslinker eliminates the trapsites on the surface, allowing a stable operation and efficient charge transport. Additionally, the solution‐processability enables the production of uniform and thin films to yield OFETs with stable and low‐voltage driving characteristics. The printed layers are also applied as gate dielectrics for floating gate memory devices and in integrated one‐transistor‐one‐transistor based memory cells, displaying their excellent memory performance. The synthesis and fabrication strategies employed in this study can become useful guidelines for the production of high‐k dielectrics for stable OFETs and other applications. Abstract : Newly synthesized nonvacuum processed high‐k polymeric dielectric materials containing carboxyl functionality are applied as gate dielectrics to manufacture very stable operating organic filed‐effect transistors. In particular, the solution‐processability of these materials induce the excellent printability via electrohydrodynamic jet printing process, and printed layers are utilized as gate dielectrics in the device, demonstrating its successful application from unit devices to integrated devices.